A hierarchical α-MoC1−x hybrid nanostructure for lithium-ion storage. Issue 17 (13th April 2017) - Chen, Junmei; Huang, Yang; Zhao, Feipeng; Ye, Hualin; Wang, Yeyun; Zhou, Junhua; Liu, Yuping; Li, Yanguang
Abstract : A chrysanthemum-inspired hierarchical α-MoC1− x hybrid represents an excellent host material for Li + ion storage. Abstract : Transition metal carbides are promising electrode materials for electrochemical energy storage, yet to unveil their full potential requires judicious structural engineering at the nanoscale. In this study, we report a chrysanthemum-inspired nanoscale design to prepare a three-dimensional hierarchical molybdenum carbide hybrid. It consisted of an ensemble of numerous nanoflakes protruding out from the center, each formed by ultra-small (∼2 nm) α-MoC1− x nanoparticles uniformly supported on a N-doped carbonaceous support. Such a hybrid material has enlarged surface areas, shortened ionic diffusion length, great mechanical robustness, and buffer room for electrode volume change. Owing to the three-dimensional hierarchical arrangement, this hybrid material exhibits impressive performance toward active lithium-ion storage. It delivers a large reversible capacity of >1000 mA h g −1, great rate capacity with significant capacity at 10 A g −1, and excellent cycling stability with >95% capacity retention after 100 cycles at 500 mA g −1 . Most impressively, we demonstrate that the structural integrity of the hybrid microflower is largely preserved even after prolonged cycling.